(untitled) (Perioperaciina Medicina, 2021)
One of the most complex problems of modern surgery is the treatment and prevention of anaerobic infection. Main place in overcoming of this infectious complication is devoted to urgent surgical intervention and correct early empiric antibacterial therapy. Special place in the combined empiric antibacterial treatment is devoted to 5-nitroimidazoles. Modern data about clinical efficacy of ornidazole in the treatment of surgical infectious complications is presented in the article. We performed a comparison of therapeutic activity and physical-chemical properties, pharmacokinetic and pharmacodynamic features of ornidazole with the first representative of 5-nitroimidazole class – metronidazole. Taking into account antiprotozoal and antianaerobic activity of ornidazole, it is recommended to be used in the schemes of combined therapy of severe generalized anaerobic infections and purulent processes of different localization; treatment and prevention of surgical infections after intraabdominal, thoracic, proctological and dental surgical interventions.